Representaciones sonoras: masculinidades y música popular en la colección de John Alden Mason, 1914-1915. - VARGAS, HUGO RENÉ VIERA (Centro Journal)
This article analyzes the representations of masculinities in Puerto Rico using the collection of popular music compiled by John Alden Mason between 1914 and 1915. It proposes that while a considerable number of these songs were instruments of socialization and reaffirmation of a hegemonic masculinity other songs represented and constructed alternative notions to this recalcitrant masculinity. In addition, the article argues that this alternative (non-hegemonic) masculinities used music as a cathartic and performative space in which singing, as opposed to speaking, created a special setting where hetero-normative gender order and the principal tenets of patriarchal masculinity were suspended. This scenario allowed men to exteriorize intimate feelings in public spaces without causing them stigmatization or social shame.